League of Filipino Students (LFS) members personality traits and reasons for joining the organization - Javelona, Mary Gold Arandilla
The popularity of the league of Filipino Students (LFS) as a distinct socio-political student organization and the zealous image projected by its members in voicing out their opinions and attitude about certain social and political issues (backed up by a preliminary survey), caught the researcher's attention and developed her interest to study its members personality traits and reasons for joining the said organization. This study concerning LFS members deals with the personality traits dominant in them as measured by the Edwards Personal Preference Schedule (EPPS), and the reasons they have for having committed themselves to the cause of the organization. This also includes the advantages and disadvantages of being a member, the importance of the LFS to them, and its significance as a student organization in our society. The responses to all theses questions are measured by an interview schedule., The respondents in this study are the individual members and officers of the LFS who are officially enrolled in any College or University in Iloilo City where the LFS exists as a student organization, either officially or unofficially recognized by the school. The total population of respondents is fifty eight (58), unevenly distributed in the four schools in the city namely University of San Agustin (15), Western Institute of Technology (13), Central Philippine University (8), and the University of the Philippines in the Visayas City and Miagao campuses (22). From these schools, a sample of thirty five (35) respondents or 60 is taken using stratified random sampling with proportional allocation. This consists 9 from USA, 7 from WIT, 5 from CPU and 14 from UPV. The respondents includes ten (10) females and twenty five (25) males. The result of the EPPS shows that respondents rated highest in autonomy which is their most dominant trait, followed by nurturance, succorance, heterosexuality, aggression, affiliation, change, intraception and exhibition (which is a little higher than the 50th percentile rank). They rated lowest in endurance. There are some variations in percentile ranks in terms of gender. In succorance for example, female respondents rated higher than the males while in aggression, the situation is reversed. This result is supportive of past studies revealing that males are more aggressive than females and the latter are more succorant than the former. The researcher tested whether there is any significant difference between male and female LFS members personality traits. Using t test for independent means, with alpha at .05 and degrees of freedom (N-1) = 35 t tabulated is 1.69 resulting to the acceptance of the null hypothesis. This means that there is no significant difference between male and female members personality traits.